A green replacement route to produce phosphatidylserine in environmentally friendly edible oil-water systems and investigations on the enzymatic mechanism - Zhang, Tiantian; Lan, Haizhi; Wang, Huan; Li, Binglin; Gand, Martin; Wang, Jiao (Journal of food science, 2024)
Phosphatidylserine (PS) has many applications in functional food and pharmaceutical industries because of its critical role in activating important signal transduction pathways and modulating neurotr...
Online veröffentlicht: 26 November 2024
Gesehen am 03.07.2025